The Effect of Green Accounting Quality on Sustainability Report with Company Size as Moderating Variable - Oktaviani, Zulmia; Sudrajat; Metalia, Mega (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This research investigates the influence of green accounting quality on sustainability reporting, with company size as a moderating variable. The study focuses on companies listed on the Indonesia Stock Exchange from 2017 to 2022, evaluating their sustainability reports using Global Reporting Initiative (GRI) standards and green accounting quality through PROPER ratings. Descriptive statistics and Moderated Regression Analysis (MRA) reveal that while green accounting quality positively impacts sustainability reporting, company size does not significantly moderate this relationship. The findings highlight the importance of green accounting in enhancing sustainability disclosures, aligning with legitimacy and stakeholder theories. However, the expected moderating role of company size was not supported, suggesting that factors such as sectoral differences and variations in environmental reporting practices may influence the results. This study contributes to understanding the dynamics between green accounting and sustainability reporting in the context of corporate environmental responsibility.